Antiarrhythmic Effects of Melatonin and Omega-3 Are Linked with Protection of Myocardial Cx43 Topology and Suppression of Fibrosis in Catecholamine Stressed Normotensive and Hypertensive Rats - Szeiffova Bacova, Barbara; Viczenczova, Csilla; Andelova, Katarina; Sykora, Matus; Chaudagar, Kiranj; Barancik, Miroslav; Adamcova, Michaela; Knezl, Vladimir; Egan Benova, Tamara; Weismann, Peter; Slezak, Jan; Tribulova, Narcisa (Antioxidants (Basel, Switzerland), 2020)
Cardiac β-adrenergic overstimulation results in oxidative stress, hypertrophy, ischemia, lesion, and fibrosis rendering the heart vulnerable to malignant arrhythmias. We aimed to explore the anti-arrhythmic efficacy of the anti-oxidative and anti-inflammatory compounds, melatonin, and omega-3, and their mechanisms of actions in normotensive and hypertensive rats exposed to isoproterenol (ISO) induced β-adrenergic overdrive. Eight-month-old, male SHR, and Wistar rats were injected during 7 days with ISO (cumulative dose, 118 mg/kg). ISO rats were either untreated or concomitantly treated with melatonin (10 mg/kg/day) or omega-3 (Omacor, 1.68 g/kg/day) until 60 days of ISO withdrawal and compared to non-ISO controls. Findings showed that both melatonin and omega-3 increased threshold current to induce ventricular fibrillation (VF) in ISO rats regardless of the strain. Prolonged treatment with these compounds resulted in significant suppression of ISO-induced extracellular matrix alterations, as indicated by reduced areas of diffuse fibrosis and decline of hydroxyproline, collagen-1, SMAD2/3, and TGF-β1 protein levels. Importantly, the highly pro-arrhythmic ISO-induced disordered cardiomyocyte distribution of electrical coupling protein, connexin-43 (Cx43), and its remodeling (lateralization) were significantly attenuated by melatonin and omega-3 in Wistar as well as SHR hearts. In parallel, both compounds prevented the post-ISO-related increase in Cx43 variant phosphorylated at serine 368 along with PKCε, which are known to modulate Cx43 remodeling. Melatonin and omega-3 increased SOD1 or SOD2 protein levels in ISO-exposed rats of both strains. Altogether, the results indicate that anti-arrhythmic effects of melatonin and omega-3 might be attributed to the protection of myocardial Cx43 topology and suppression of fibrosis in the setting of oxidative stress induced by catecholamine overdrive in normotensive and hypertensive rats.
Keywords: isoproterenol; ventricular fibrillation; omega-3 fatty acids; connexin-43; extracellular matrix; rat heart; melatonin